2021
DOI: 10.1002/rcm.9084
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of rapid, sensitive, and quantitative liquid chromatography‐electrospray ionization‐tandem mass spectrometry method coupled with liquid–liquid extraction for measurement of urinary bisphenol A, 4‐t‐octylphenol, and 4‐nonylphenol

Abstract: Rationale Bisphenol A (BPA), 4‐t‐octylphenol (4‐t‐OP), and 4‐nonylphenol (4‐NP) are ubiquitous manufactured chemicals classified as endocrine disruptors. Now these substances are prevalent and found in a wide range of biological and environmental matrices globally. Acting as xenoestrogens, their target is to bind estrogen receptors and compete against natural hormones. Thus, there is an increasing concern on their negative health consequences. Methods A rapid, sensitive, and robust method was established, vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In real sample analysis, complex matrices and low concentration levels of analytes are key limitations for determination by chromatography and spectrometry, and sample pretreatment or preconcentration is required. Sample preparation methods developed for the adsorption/extraction of antioxidants and BPA include solid-phase extraction (SPE), 6 dispersive solid-phase extraction (DSPE), 7 solid-phase microextraction, 8 liquid-liquid extraction, 9 and magnetic solidphase extraction (MSPE), [10][11][12] dispersive liquid-liquid microextraction (DLLME), 13 and microextraction using deep eutectic solvents (DESs). 14 Compared to SPE and LLE, MSPE is more suitable for large volumes of sample solution.…”
Section: Introductionmentioning
confidence: 99%
“…In real sample analysis, complex matrices and low concentration levels of analytes are key limitations for determination by chromatography and spectrometry, and sample pretreatment or preconcentration is required. Sample preparation methods developed for the adsorption/extraction of antioxidants and BPA include solid-phase extraction (SPE), 6 dispersive solid-phase extraction (DSPE), 7 solid-phase microextraction, 8 liquid-liquid extraction, 9 and magnetic solidphase extraction (MSPE), [10][11][12] dispersive liquid-liquid microextraction (DLLME), 13 and microextraction using deep eutectic solvents (DESs). 14 Compared to SPE and LLE, MSPE is more suitable for large volumes of sample solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, accumulation of trace levels of BPA in the body causes irreparable effects which highlights the application of potent sample pretreatment techniques for separation and preconcentration of trace/ultra-trace BPA in food samples. Various sample pretreatment methods such as liquid–liquid extraction, 8 solid phase extraction, 9 liquid phase microextraction, 10 dispersive liquid–liquid microextraction, 11 and homogeneous liquid–liquid microextraction, 12 have been reported for the separation of BPA before analysis in various matrices. However, few studies have been reported for the determination of BPA in food samples which are required to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The omnipresence of bisphenols in everyday life has necessitated the development of methods for their biomonitoring in various matrices, both in body fluid and solid tissues, such as urine, serum, breast milk, sperm, and hair. This has led to the development of numerous sample preparation techniques, such as the Quick Easy Cheap Effective Rugged Safe (QuEChERS) procedure [10][11][12][13][14], liquid-liquid extraction (LLE) [15][16][17], solidphase extraction (SPE) [18][19][20][21][22][23][24], on-line SPE [25,26], dispersive liquid-liquid microextraction (DLLME) [27][28][29], and more. The low concentration of analytes found in biological samples combined with complex matrices requires not only effective sample preparation but also a very sensitive and reliable separation technique, such as liquid chromatography or gas chromatography.…”
Section: Introductionmentioning
confidence: 99%